Demanda energética em diferentes manejos de solo e híbridos de milho - Riquetti, Neilor Bugoni [UNESP] (2012)
This study aimed to account the energy balance of six different farming systems: CMT (minimum tillage with transgenic corn); CMNT (minimum tillage with non-transgenic corn); PCT (conventional tillage with transgenic corn); PCNT (conventional tillage with non-transgenic corn); PDT (no-tillage system with transgenic corn) and PDNT (no-tillage system with non-transgenic corn). The study was carried out at the Experimental Farm Lageado FCA/Unesp, Botucatu - SP. The energy balance was performed by subtracting the total energy inputs by the total energy output. Energy efficiency was calculated by dividing the total energy output by the total energy inputs. The total values ​​of energy inputs and outputs were expressed in MJ.ha-1 (mega joules per hectare). To calculate the energy inputs were accounted the fuel consumption and lubricants, depreciation energy of machinery and implements, manpower and agricultural inputs. The energy outputs were calculated according to the maize yield. The result shows that the system PDT was the system that had better energy efficiency and the system that had the lowest efficiency was the PCT system. The system with lower energy demand was the PDT and the greatest demand was PCNT.